Anti-Tuberculosis Drug Adherence Among Pulmonary Tuberculosis Patients At Primary Health Center - Zannah, Junnia Aulia; Yuliawati, Yuliawati; Efendi, M Rifqi; Pondawinata, Marizki; Sani, Fathnur (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2026)
Background: Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium tuberculosis (M. tb). This bacterium has characteristics that make it difficult to treat, resulting in prolonged TB therapy. Non-adherence to anti-tuberculosis drugs (ATD) may increase the risk of treatment failure in patients diagnosed with pulmonary TB, which in turn can elevate the risk of multidrug resistance (MDR). Method: This study is a descriptive observational research with a cross-sectional design and consisted of 45 participants. The research instrument used was the MMAS-8 (Morisky Medication Adherence Scale) questionnaire. Univariate and bivariate analyses were performed using the Chi-Square test. Result: The results showed that 34 respondents (75.6%) had a high level of adherence, 9 respondents (20%) had a moderate level of adherence, and 2 respondents (4.44%) had a low level of adherence. According to statistical analysis using the Chi-Square test, the significance value for gender and adherence was 0.822, for age and adherence was 0.031, for educational level and adherence was 0.445, and for occupation and adherence was 0.465. Conclusion: The majority of TB patients at Puskesmas Kenali Besar demonstrated a high level of adherence.